Distribution of ciliary adaptor proteins tubby and TULP3 in the organ of Corti - Lindner, Laura A.; Derstroff, Dennis; Oliver, Dominik; Reimann, Katrin (Frontiers in Neuroscience, 2023)
Tubby-like proteins are membrane-associated adaptors that mediate directional trafficking into primary cilia. In inner ear sensory epithelia, cilia - including the hair cell’s kinocilium - play important roles as organizers of polarity, tissue architecture and cellular function. However, auditory dysfunction in tubby mutant mice was recently found to be related to a non-ciliary function of tubby, the organization of a protein complex in sensory hair bundles of auditory outer hair cells (OHCs). Targeting of signaling components into cilia in the cochlea might therefore rather rely on closely related tubby-like proteins (TULPs). In this study, we compared cellular and subcellular localization of tubby and TULP3 in the mouse inner ear sensory organs. Immunofluorescence microscopy confirmed the previously reported highly selective localization of tubby in the stereocilia tips of OHCs and revealed a previously unnoticed transient localization to kinocilia during early postnatal development. TULP3 was detected in the organ of Corti and vestibular sensory epithelium, where it displayed a complex spatiotemporal pattern. TULP3 localized to kinocilia of cochlear and vestibular hair cells in early postnatal development but disappeared subsequently before the onset of hearing. This pattern suggested a role in targeting ciliary components into kinocilia, possibly related to the developmental processes that shape the sensory epithelia. Concurrent with loss from kinocilia, pronounced TULP3 immunolabeling progressively appeared at microtubule bundles in non-sensory Pillar (PCs) and Deiters cells (DC). This subcellular localization may indicate a novel function of TULP proteins associated with the formation or regulation of microtubule-based cellular structures.